2022
DOI: 10.1007/jhep06(2022)062
|View full text |Cite
|
Sign up to set email alerts
|

Damping signatures at JUNO, a medium-baseline reactor neutrino oscillation experiment

Abstract: We study damping signatures at the Jiangmen Underground Neutrino Observatory (JUNO), a medium-baseline reactor neutrino oscillation experiment. These damping signatures are motivated by various new physics models, including quantum decoherence, ν3 decay, neutrino absorption, and wave packet decoherence. The phenomenological effects of these models can be characterized by exponential damping factors at the probability level. We assess how well JUNO can constrain these damping parameters and how to disentangle t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 79 publications
(158 reference statements)
0
8
0
Order By: Relevance
“…(1.1) by an order of magnitude. The JUNO collaboration itself, following the analysis of [6], has studied the expected sensitivity of their experiment to various mechanisms of damping of neutrino oscillations, including damping due to neutrino WP separation [4]. They concluded that JUNO should be able to set the limits σ p /p < 1.04 × 10 −2 and σ x > 2.3 × 10 −10 cm, both at 95% C.L.…”
Section: Jhep11(2022)082mentioning
confidence: 99%
See 2 more Smart Citations
“…(1.1) by an order of magnitude. The JUNO collaboration itself, following the analysis of [6], has studied the expected sensitivity of their experiment to various mechanisms of damping of neutrino oscillations, including damping due to neutrino WP separation [4]. They concluded that JUNO should be able to set the limits σ p /p < 1.04 × 10 −2 and σ x > 2.3 × 10 −10 cm, both at 95% C.L.…”
Section: Jhep11(2022)082mentioning
confidence: 99%
“…The fragments quickly thermalize on the time scale that is many orders of magnitude shorter than their lifetimes τ N with respect to β-decay. 4 Therefore, at the moment of the decay the parent nuclei are in thermal equilibrium with the medium, and their velocities are determined by the temperature of the medium T . For a fragment of mass m N the average velocity is…”
Section: Neutrino Wps In the Case Of Delocalized Accompanying Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the phenomenology part of neutrino decoherence, roughly speaking, measurements of neutrinos produced in both long and short baseline experiments and in the atmosphere are best fitted with neutrinos considered as fully coherent, see for instance [36] for an updated global fit; as for neutrinos produced outside the Earth, such as solar and supernova neutrinos, it is best described as fully incoherent. There are also many discussions on neutrino decoherence phenomenons, such as general neutrino decoherence for reactor experiments in [37][38][39]; gravitation fluctuation or cosmological effects causing atmospheric neutrino decoherence in [18,[40][41][42]; matter effect responsible for accelerator or atmospheric JHEP08(2022)111 neutrino decoherence in [22,[43][44][45][46]. Our structure carries the potential of including all the mechanisms above and more, since both the QFT approach and the open quantum system concept is included.…”
Section: Jhep08(2022)111mentioning
confidence: 99%
“…This is because it has less uncertainty compared to the Double Chooz experiment and a less complicated structure for the distribution of reactors and detectors compared with the Daya Bay experiment, which would affect the damping signature through σ L in a non-trivial way, see appendix D. In addition, different dependence on L 0 and E 0 in the damping signatures in neutrino oscillation is discussed in e.g. [39,62].…”
Section: Jhep08(2022)111 4 Phenomenology Of Neutrino Decoherencementioning
confidence: 99%